Analisis Nisbah Kerjasama Umkm Dalam Konteks Musyarakah Di Food Court Toserba Yogya Purwakarta - Rachma Frattiwi (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
This research was conducted at the Yogya Purwakarta Toserba Food Court. The problem that occurred at the Yogya Purwakarta Toserba Food Court was that the concept of the collaboration agreement that was carried out tended to be wrong. The purpose of this study was first to determine the cooperation agreement undertaken by the UMKM with the "Yogya Rasa", namely the system of cooperation agreements for results. Cooperation agreement for profit sharing here is a cooperation agreement made by one party with another party. Where one party provides facilities or infrastructure in the form of a place in the form of a counter while the other party occupies the counter with a profit sharing system. second to find out the suitability of the Musyarakah contract concept. The cooperation agreement that has been carried out by the UMKM with the manager of Yogya Toserba Food Court is in accordance with the Syirkah Mudharabah concept in which this collaboration is carried out by the first party contributing capital and work at the same time while the second party only contributes only venture capital while profits are shared according to mutual agreement. This research uses descriptive qualitative analysis approach method. Data collection can be done by the method of observation, interviews and documentation